ÍNDICE DE QUALIDADE DA ÁGUA PARA BACIAS HIDROGRÁFICAS URBANAS - LUIZ GUILHERME MAIOLINO LACERDA DE BARROS (2022)
Urban water bodies suffer several risks because of accelerated urbanization. To manage this expansion in a sustainable way, laws and management plans have been created and thus the demand for adequate monitoring of urban water is growing and should be constantly improved with the adoption of regionalized quality indexes. Through the analysis of a historical series of secondary data it was noted that the quality index used in urban streams does not have a good sensitivity to possible isolated variations of quality parameters even when these exceed the limits of the class of framework of the water body analyzed. Thus, the present work had as its objective the idealization of a water quality index that was sensitive to the limits established by the legislation in force. The development of the index was composed of four parts: selection of parameters; method of dimensioning; selection of weights; and aggregation method. The parameters total nitrogen, total solids and temperature were replaced by the parameter’s ammonia, nitrate, and surfactant. In addition, new normalization curves were created, and the weights used in the non-equal geometric method were changed. Finally, a robust index was developed to assist in public decision-making regarding surface water quality.